2019
DOI: 10.3390/ijerph16203805
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Incidence Rates in North Dakota are Associated with Land and Water Use

Abstract: Objective: The increasing rate of thyroid cancer diagnoses in the U.S. reflects the increasing use of ultrasonography and of specialist medical care. North Dakota is a rural state with limited access to specialist care, yet its incidence of thyroid cancer is significantly greater than that of the U.S. overall. We sought to identify factors responsible for the high incidence of thyroid cancer in North Dakota. Methods: We examined county-specific incidence rates for thyroid cancer in North Dakota in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In the middle of the last century, the USA conducted a large number of atmospheric nuclear tests in Nevada and New Mexico. Radioactive dust generated by nuclear tests, such as radioactive iodine, may blown to pastures in the Midwest, and polluted local water sources [ 19 ], and the ionizing radiation was the best-known exposure factor in TC. In addition, due to a large number of applications in chemical pesticides, the environmental pollution is increasing, including nitrate pollution in water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the middle of the last century, the USA conducted a large number of atmospheric nuclear tests in Nevada and New Mexico. Radioactive dust generated by nuclear tests, such as radioactive iodine, may blown to pastures in the Midwest, and polluted local water sources [ 19 ], and the ionizing radiation was the best-known exposure factor in TC. In addition, due to a large number of applications in chemical pesticides, the environmental pollution is increasing, including nitrate pollution in water.…”
Section: Discussionmentioning
confidence: 99%
“…Similar report was also discovered in Wisconsin [ 33 ]. A study from North Dakota has also shown that the increased incidence of TC may also be related to urban water use [ 19 ]. We found that most of the states with a continuous increasing TC incidence were located in the Midwest regions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to iodine nutrition factors, the relationship between residents' annual income and thyroid cancer in some research remains controversial (40)(41)(42) . In the present study, economic level was positively correlated with thyroid cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only four studies have examined the association between radon and thyroid cancer. [71][72][73][74] All studies have been ecological, and none has found an association between radon and thyroid cancer. Similarly, Ron et al reviewed five cohort studies examining environmental radiation exposure and found no association with thyroid cancer.…”
Section: Thyroid Cancermentioning
confidence: 99%